1991
DOI: 10.1136/bmj.302.6772.313
|View full text |Cite
|
Sign up to set email alerts
|

Integration of hepatitis B vaccination into rural African primary health care programmes.

Abstract: Results-Vaccine coverage for hepatitis B dropped sharply from 99% to 53% to 39% for the first, second, and third doses respectively. In contrast, vaccine coverage was maintained at 97-99% for the three doses of poliomyelitis vaccine. Serological evaluation of vaccine efficacy showed that only 3-5% of recipients of all three doses failed to develop antibodies to hepatitis B surface antigen. Only 6-6% of vaccine recipients were vaccinated according to either the early or later schedules whereas 93 4% received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, the coverage in the routine vaccination schedule for BCG inoculation during the same period was 86% and that for polio 97-99o/o. 23 In South Africa, urbanisation of black Africans has been accompanied by a substantial decline in HBV carriage. This unexpected bonus has been paralleled by a fall in the incidence of hepatocellular carcinoma.24 As shown from data obtained in Soweto,14 the decrease in the carrier rate starts with the first generation born in the urban environment.…”
Section: Possibilities For Eradication Versus Comprehensive Controlmentioning
confidence: 99%
“…However, the coverage in the routine vaccination schedule for BCG inoculation during the same period was 86% and that for polio 97-99o/o. 23 In South Africa, urbanisation of black Africans has been accompanied by a substantial decline in HBV carriage. This unexpected bonus has been paralleled by a fall in the incidence of hepatocellular carcinoma.24 As shown from data obtained in Soweto,14 the decrease in the carrier rate starts with the first generation born in the urban environment.…”
Section: Possibilities For Eradication Versus Comprehensive Controlmentioning
confidence: 99%
“…Details regarding the epidemiology of hepatitis B virus infection in children from Southern Africa has been reported in a number of published studies [Prozesky et al, 1983;Botha et al, 1984;Di Bisceglie et al, 1986;Abdool Karim et al, 1988, 1989Dusheiko et al, 1989aDusheiko et al, , 1989bJoubert et al, 1991;Schoub et al, 1991Schoub et al, , 1993Schoub, 1992]. Previous exposure to HBV as measured by HBsAg positivity ranges from 0.97% in urban black children [Di Bisceglie et al, 1986] to 25.1% in institutionalized children from Kwazulu-Natal [Abdool Karim et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B vaccination programs were not only effective in preventing perinatal and early horizontal transmission of HBV but also resulted in decreasing mortality due to fulminant hepatitis and reduced development of childhood hepatocellular carcinoma. One study in South Africa, 568 however, determined that the intervention was not effective. Some reasons for the lack of effectiveness were given, and the authors proposed that the problems they identified were likely to be faced by other programs in developing nations.…”
Section: Hepatitis B Vaccinationmentioning
confidence: 99%
“…Total cost per child immunized using the Uniject device was US $6.57 vs US $7.19 using a standard disposable syringe at the health center. Schoub et al 568 South Africa; rural setting; communitybased QT All infants born in 1989 in a self-governing region of the Transvaal were immunized according to 2 schedules: (1) early schedule ϭ birth, 3 mo and 6 mo and (2) late schedule ϭ 3 mo, 4.5 mo and 6 mo. Those who were not given vaccine according to any 1 of these schedules were classified as unscheduled.…”
Section: Odusanya Et Al 725mentioning
confidence: 99%